Adapting institutions governance, complexity, and social-ecological resilience - Boyd, Emily; Folke, Carl (Cambridge University Press, 2011)
Global environmental change is occurring at a rate faster than humans have ever experienced. Climate change and the loss of ecosystem services are the two main global environmental crises facing us today. As a result, there is a need for better understanding of the specific and general resilience of networked ecosystems, cities, organisations and institutions to cope with change. In this book, an international team of experts provide cutting-edge insights into building the resilience and adaptive governance of complex social-ecological systems. Through a set of case studies, it focuses on the social science dimension of ecosystem management in the context of global change, in a move to bridge existing gaps between resilience, sustainability and social science. Using empirical examples ranging from local to global levels, views from a variety of disciplines are integrated to provide an essential resource for scholars, policy-makers and students, seeking innovative approaches to governance